Impact of Indian Climate in Terms of Temperature Humidity Index on Reproductive and Semen Parameters of Barbari Bucks - Shastri, Shriya; Chouksey, Shivika; Chourasiya, Mona; Nidhi Shukla, Satya (The Indian Journal of Animal Reproduction, 2025)
The present study was conducted to investigate the effect of temperature-humidity index on the reproductive and semen  parameters of Barbari bucks. Twelve adult Barbari bucks aged between 1.5 to 4.0 years were selected and managed under  a semi-intensive system. A total of 288 ejaculates were collected from the chosen bucks during the experiment. Detailed  sexual characteristics and breeding behaviors were recorded during semen collection. Immediately after collection, the  initial evaluation of the semen samples was carried out within 10 min, and then the sample was diluted with a Tris-based  semen extender (TCEYG Buffer). The temperature humidity index (THI) was calculated to evaluate its effect on reproductive parameters. The result reveals that there was mild stress in the August and September months, whereas no stress  was seen in other months of the study period. Correlation between climatic parameters with different semen parameters  and the data showed that relative humidity was highly significant (p ≤ 0.01) and negatively correlated with pH. However,  other climatic parameters were negatively correlated with seminal parameters.
Keywords: Barbari buck; Temperature humidity index; Heat stress; Semen